Recommendations on: internal standard criteria, stability, incurred sample reanalysis and recent 483s by the Global CRO Council for Bioanalysis. (June 2011) - Lowes, Steve; Jersey, Jim; Shoup, Ronald; Garofolo, Fabio; Savoie, Natasha; Mortz, Ejvind; Needham, Shane; Caturla, Maria Cruz; Steffen, Ray; Sheldon, Curtis; Hayes, Roger; Samuels, Tim; et al.
"" The Global CRO Council (GCC) for Bioanalysis was formed in an effort to bring together many CRO leaders to openly discuss bioanalysis and the regulatory challenges unique to the outsourcing industry ""